QUALITY MANAGEMENT OF ENVIRONMENTAL PROTECTION IN THE ACTIVITY OF SUPREME AUDIT INSTITUTIONS IN VARIOUS STATES AND THE PROSPECTS FOR IMPROVING THE QUALITY BASED ON INDUSTRIAL AND MANUFACTURING ENGINEERING - Nina P. Efimova (Center for Quality, Faculty of Engineering, University of Kragujevac, Serbia, 2021)
The paper is aimed at identifying the prospects for improving the quality based on industrial and manufacturing engineering, as well as developing recommendations to improve the quality management of environmental protection in the activity of supreme audit institutions in various states based on industrial and manufacturing engineering. The originality of the research is attributable to the focus on the quality and prospects for improving it in environmental protection in the activity of supreme audit institutions in various states. The paper not only justifies the need for improving the quality, but also identifies accurate quantitative benchmarks (reference values of quality indicators and their factors), gives applied recommendations to improve the quality of environmental protection in the activity of supreme audit institutions in various states based on industrial and manufacturing engineering. The authors' recommendations are oriented toward a realistic (feasible) scenario and involve ensuring the beneficial effect of industrial and manufacturing engineering by increasing the degree of beneficial effect of industrial and manufacturing engineering factor to 100 points (+31.19 %). This will cause an increase in the strength of auditing and accounting standards to 15.95% and an increase in the degree of renewable energy regulation to 11.19%. As a result, this allows decreasing the level of environmental pollution by 42.08% and increasing the Climate Index to 5.39%.